Is critique secular? : Blasphemy, injury, and free speech - Asad, Talal; Brown, Wendy, 1955-; Butler, Judith, 1956-; Mahmood, Saba, 1962-2018 (Fordham University Press, 2013)
Four leading thinkers confront the paradoxes and dilemmas attending the supposed stand-off between Islam and liberal democratic values.